If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 3) + -2(x + -4) = 2x + -1 Reorder the terms: 5(3 + 2x) + -2(x + -4) = 2x + -1 (3 * 5 + 2x * 5) + -2(x + -4) = 2x + -1 (15 + 10x) + -2(x + -4) = 2x + -1 Reorder the terms: 15 + 10x + -2(-4 + x) = 2x + -1 15 + 10x + (-4 * -2 + x * -2) = 2x + -1 15 + 10x + (8 + -2x) = 2x + -1 Reorder the terms: 15 + 8 + 10x + -2x = 2x + -1 Combine like terms: 15 + 8 = 23 23 + 10x + -2x = 2x + -1 Combine like terms: 10x + -2x = 8x 23 + 8x = 2x + -1 Reorder the terms: 23 + 8x = -1 + 2x Solving 23 + 8x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 23 + 8x + -2x = -1 + 2x + -2x Combine like terms: 8x + -2x = 6x 23 + 6x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 23 + 6x = -1 + 0 23 + 6x = -1 Add '-23' to each side of the equation. 23 + -23 + 6x = -1 + -23 Combine like terms: 23 + -23 = 0 0 + 6x = -1 + -23 6x = -1 + -23 Combine like terms: -1 + -23 = -24 6x = -24 Divide each side by '6'. x = -4 Simplifying x = -4
| 2(x+2)(x-4)4=0 | | -34=42+-4v | | (X+3)(X+4)(X+5)=0 | | (X-3)(Y+7)=0 | | 6(5-2y)-5(y+3)= | | 5x-(x-18)=6-2(x+15) | | x*(x+1)(x+2)(x+3)=0.5625 | | 4(2+3)-2y= | | X^3-3x^2+x+1=0 | | -16-8(2a+3)=23-2a | | 4(2+3)-2y=3(4y+3) | | -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 | | y=40ln(3x+8) | | 12-2u=8u+45 | | 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 |